N,N′-Bis(4-chloro-3-fluorobenzylidene)ethane-1,2-diamine - Kia, Reza (International Union of Crystallography, 2008)
The asymmetric unit of the title Schiff base compound, C(16)H(12)Cl(2)F(2)N(2), contains one half of the centrosymmetric molecule. Molecules related by translation along the a axis form stacks with short intermolecular C⋯C distances of 3.429 (3) Å. The crystal packing also exhibits short intermolecular Cl⋯F contacts of 3.087 (1) Å.